Growth of Carbon Nanocoils by Porous α-Fe2O3/SnO2 Catalyst and Its Buckypaper for High Efficient Adsorption - Zhao, Yongpeng; Wang, Jianzhen; Huang, Hui; Cong, Tianze; Yang, Shuaitao; Chen, Huan; Qin, Jiaqi; Usman, Muhammad; Fan, Zeng; Pan, Lujun (Nano-Micro Letters, 2020)
High-purity (99%) carbon nanocoils (CNCs) have been synthesized by using porous α-Fe2O3/SnO2 catalyst. The yield of CNCs reaches 9,098% after a 6 h growth. This value is much higher than the previously reported data, indicating that this method is promising to synthesize high-purity CNCs on a large scale. It is considered that an appropriate proportion of Fe and Sn, proper particle size distribution, and a loose-porous aggregate structure of the catalyst are the key points to the high-purity growth of CNCs. Benefiting from the high-purity preparation, a CNC Buckypaper was successfully prepared and the electrical, mechanical, and electrochemical properties were investigated comprehensively. Furthermore, as one of the practical applications, the CNC Buckypaper was successfully utilized as an efficient adsorbent for the removal of methylene blue dye from wastewater with an adsorption efficiency of 90.9%. This study provides a facile and economical route for preparing high-purity CNCs, which is suitable for large-quantity production. Furthermore, the fabrication of macroscopic CNC Buckypaper provides promising alternative of adsorbent or other practical applications. Highlights: 1 High-purity ( 99%) carbon nanocoils (CNCs) without the amorphous carbon layer were synthesized by using porous α-Fe2O3/SnO2 catalyst. 2 The highest yield of the CNCs can reach 9098% after a 6 h growth, which is much higher than those mentioned in previous reports. 3 A CNC Buckypaper was successfully prepared and utilized as an efficient adsorbent for the removal of methylene blue dye with the adsorption efficiency of 90.9%.